Acid–base core–shell microspheres are incorporated into proton exchange membranes to effectively alleviate the rapid decline in proton conductivity at low humidity. (March 2021) - Sun, Xiang; Zhu, Fan; Liu, Xiaoyang; Ren, Hongqian; Xia, Minglong; Yang, Mengjie; Feng, Yi; Ding, Huili
The development of a proton exchange membrane (PEM) that can avoid rapid decay of proton conductivity under low humidity is of great significance for the practical application of PEMFC. In this study, acid–base core–shell microspheres (PCSMs-MA@TAC) with a carboxylic acid core and a triazine shell were synthesized by distillation-precipitation polymerization using cross-linked carboxylic acid microspheres (PMAA) as seeds. These PCSMs were then incorporated into a sulfonated poly(ether ether ketone) matrix to make hybrid membranes. Incorporation of PCSMs microspheres can not only strengthen the vehicle mechanism by increasing the water uptake of the membrane, but also the acid–base pairs formed at the SPEEK/PCSMs interface provide a new low-energy barrier pathway for proton hopping, thereby enhancing the proton conduction of the Grotthuss mechanism. The results show that when the content is 10 wt%, the proton conductivity of the SPEEK/PCSMs-MA@TAC composite membrane can reach 0.161 S cm −1 at 80°C and 100% RH, which is 19.3% higher than the SPEEK control membrane (0.135 S cm −1 ). In particular, even at 60% RH, the proton conductivity of the SPEEK/PCSMs-MA@TAC-10 composite membrane is still 67 mS cm −1, which is 3.16 times higher than that of the SPEEK membrane. Therefore, the SPEEK/PCSMs-MA@TAC composite membrane can maintain superior performance even under high temperature and low humidity conditions.